“How Do We Start? And How Will They React?” Disclosing to Young People with Perinatally Acquired HIV in Uganda - Namukwaya, Stella; Paparini, Sara; Seeley, Janet; Bernays, Sarah (Frontiers in Public Health, 2017)
Despite great advances in paediatric HIV care, rates and the extent of full disclosure of HIV-status to infected children remain low especially in resource-constrained setting. The World Health Organisation (WHO) recommends that, by the age of 10-12 years old, children should be made fully aware of their HIV positive status. However, this awareness is often delayed until much later in their adolescence. Few studies have been conducted to investigate what influences caregivers’ decision-making process in this regard in low income settings. In this paper, we present an analysis of care dyads of caregivers and HIV positive young people in Kampala, Uganda, as part of the findings of a longitudinal qualitative study about young people's adherence to antiretroviral therapy embedded in an international clinical trial (BREATHER). Repeat in-depth interviews were conducted with 26 young people living with HIV throughout the course of the trial and once-off interviews with 16 of their caregivers were also carried out towards the end of the trial. In this article, we examine why and how caregivers decide to disclose a young person’s HIV-status to them, and explore their feelings and dilemmas towards disclosure, as well as how young people reacted and the influence it had on their relationships with and attitudes towards their caregivers. Caregivers feared the consequences of disclosing the young person’s positive status to them and disclosure commonly occurred hurriedly in response to a crisis, rather than as part of an anticipate and planned process. A key impediment to disclosure was that caregivers feared that disclosing would damage their relationships with the young people and commonly used this as a reason to continue to postpone disclosure. However young people did not report prolonged feelings of blame or anger towards their caregivers about their own infection, but they did express frustration at the delay and obfuscation surrounding the disclosure process. Our findings can inform the ways in which mainstream HIV services support caregivers through the disclosure process. This includes providing positive encouragement to disclose fully and to be more confident in initiating and sustaining the timely process of disclosure.